Processos de tornar-se pesquisadora da própria experiência: indícios narrativos de professoras que ensinam matemática - Leandro, Everaldo Gomes (Universidade Federal de São Carlos, 2020)
Camille was born in the city of Getúlio Vargas in Rio Grande do Sul. Nádia is from Minas Gerais just like me. Maria Auxiliadora, or rather, Dora Megid is from São Paulo. Camille studied while her parents were at the mate's wheel. Dora Megid was a very good student in mathematics and was literate in the Montessori method. Nádia lost her father at a very young age and he said things like: a woman has to study to be someone in life. Camille learned to play the piano. Dora Megid and Nádia have grandchildren. Camille lived in Curitiba, Nádia in Porto Velho. Camille earned a bachelor's degree and read texts in other languages. Dora Megid studied at a school for nuns. Nádia suffered to get a job during the Military Dictatorship, while Dora Megid took to the streets to protest. At that time, Camille was not even born. A priest was an example for Nádia. Lots of memories... But what do these women have in common? Camille, Nádia and Dora Megid, each following their own path, became teachers who teach mathematics and research their own experiences. The present study aimed to understand the processes of becoming a researcher of her own experience based on the narrative evidence left by these teachers. Narrative clues are the clues and signs found in the narratives of Camille, Nádia and Dora Megid. The narrative evidence made it possible to answer the question: how did teachers who teach mathematics become researchers of their own experience? The teachers' narratives confirmed the following thesis: “being a teacher who teaches mathematics in the 21st century, for the participants of this research, is related to the construction of a professional posture that understands the need to be a researcher of her own experience, considering objective and subjective conditions of life that enable processes of becoming a research teacher”. To face a narrative is to be surprised...
Processes of becoming a researcher of her own experience: narrative evidence from teachers who teach mathematics
Keywords: Educação matemática; Professoras pesquisadoras da própria experiência; Pesquisa narrativa; Paradigma indiciário; Pesquisa da própria prática; Mathematical education; Researcher teachers from their own experience; Narrative research; Evidentiary paradigm; Research of own practice; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO